Bright, Stable, and Biocompatible Organic Fluorophores Absorbing/Emitting in the Deep Near‐Infrared Spectral Region. Issue 11 (31st January 2017) - Lei, Zuhai; Li, Xinran; Luo, Xiao; He, Haihong; Zheng, Jing; Qian, Xuhong; Yang, Youjun
Abstract: Small‐molecule organic fluorophores spectrally active in the 800–950 nm region are sought‐after for their broad potential in biomedical and material applications. We have developed a new family of brightly fluorescent dyes (ECX ) to meet this challenge.ECX dyes are transparent to the visible region, while strongly absorbing in the NIR region at approximately 880 nm. They emit at around 915 nm with a fluorescence quantum yield up to 13.3 %.ECX dyes exhibit high chemostability, high photostability, and low tendency to aggregate. Other merits ofECX dyes include low degree of solvatochromism and facile post‐synthetic derivatization.ECX dyes potentially make available the 800–950 nm region for spectroscopic and microscopic applications and are also expected to find broad material applications. Abstract : Deep into NIR : A class of bright and stable small‐molecule organic fluorophores absorbing and emitting at around 880 nm and 915 nm, respectively, was developed. The dyes are suitable for in vitro and in vivo imaging, and make available the red end of the biological NIR spectral window for microscopic studies. They are also potentially valuable for a range of material‐based applications.